Pengaruh Komite Audit Memoderasi Ukuran Perusahaan Terhadap Pengungkapan Sustainability Report - Hati, Herwinda Anggun Permata; Susilowati, Endah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study examines the effect of firm size on sustainability report disclosure, with the audit committee as a moderating variable. The background of this research stems from the generally low and varied levels of sustainability disclosure in Indonesia, as well as the crucial role of internal oversight in supporting sound corporate governance practices. The research sample consists of 37 mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, selected using purposive sampling. Data were collected through documentation of annual reports and sustainability reports, and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 3 software. The results show that both firm size and the audit committee significantly affect sustainability report disclosure, as supported by a p-value of 0.000. Furthermore, the audit committee is proven to moderate and strengthen the relationship between firm size and sustainability disclosure, with a p-value of 0.044. These findings highlight the important role of the audit committee in promoting transparency of non-financial information and reinforcing the implementation of good corporate governance, particularly in the mining sector.